Educação para o pensar como política educacional para a educação básica - Tonieto, Carina (2010)
This research,linked to the line of research Educational Policy, aims to investigate the possibilityof the Education fo Thinking Program becomes an educational policy for basic education, trying to answer the following question: how can the Education for Thinking Program become a productive educational policy to face the current ducational context? In order to produce a suitable response to the proposed problem, we try to develop a reading of the educational context and of the school daily whose reference are questions related to (i) the production of knowledge (epistemological aspects), (ii) the process of school management organizational aspects)and (iii) the moral-ethic education. We understand that every educative proposal which intends to constitute itself as an educational policy and to develop itself as an educative project capable to orient school practices must be able to respond meaningfully to these three dimensions, which are constitutive of the educational school processes. Thus, we believe that there are, in the elements of Education for Thinking Program (the theoretic-methodological proposal that allows the higher-order thinking, the transformation of classrooms into communities of inquiry and the effective pedagogical practice which leads to critical, creative and careful thinking), the necessary ingredients to make the school space an environment that promotes the cognitive development, the experience of democracy and the moral development of students. Thus, given the possibility of Lipman s proposal of educating for thinking becomes an educational policy and a process in school daily, we see the necessity of an effective action in two areas: construction of an educative project for school and adequate formation of educators